Perancangan Aplikasi Pendeteksi Kesalahan Perintah SQL Query Menggunakan Algoritma Knuth Morris Pratt - Guidio Leonarde Ginting; Dian Puspita Napitupulu; Pristiwanto Pristiwanto (JURIKOM (Jurnal Riset Komputer), 2018)
Database Server applications are now widely used by institutions or institutions for various purposes. Most users detect the typing error manually so it is less effective. The problem that often occurs is writing or typing due to the sensitivity of the programming language. For example uppercase and lowercase letters, periods and commas, or other punctuation marks. Apart from these problems users of the MySQL application generally use tools to assist in database creation or in the manipulation process so that the Query structure of SQL is often forgotten. The Knuth-Morris Pratt algorithm is an algorithm used to perform string matching processes. This algorithm is an Exact String Matching Algorithm type which is matching strings correctly with the arrangement of characters in a matched string having the number or sequence of characters in the same string. The Knuth-Morris Pratt algorithm is part of the string search process that plays an important role in detecting errors faster and more efficiently. To find out the SQL typing error using the SQL command error detection application, the user first enters the SQL file containing the database structure. After that, the user also types in the SQL Query to be checked. Through this step, a comparison is made between the queries inputted by users with the SQL structure.